The effect of preparation and characterisation of polyurea grease. (May 2015) - Dai, X. Z.; Guo, P.; Hong, D. M.; Hui, J. D.; Hui, Z. M.; Geng, F.
<x content-type="archive" xml:space="preserve">Abstract</x> There are many factors that affect the performance of polyurea grease, such as gelatiniser, base oil, additives, material production process and the formulations. In this study, the preparation of polyurea grease is mainly investigated by changing the production process, which include the refining temperature, the mode of adding of cooling oil, the cooling methods and the frequency of grinding. Meanwhile, the kinds of base oil are also studied. The characteristics of cone penetration, steel net oil, extreme pressure and antiwear properties, water resistance, etc. were studied. The prepared polyurea grease shows a high dropping point, good water resistance, corrosion resistance and very high extreme pressure and antiwear properties.